In the Hunt for Therapeutic Targets. Issue 1 (January 2015) - Weiss, Ido D.; Ella, Ezra; Dominsky, Omri; Smith, Yoav; Abraham, Michal; Wald, Hanna; Shlomai, Zippora; Zamir, Gideon; Feigelson, Sara W.; Shezen, Elias; Bar-Shai, Amir; Alon, Ronen; et al.
<x xml:space="preserve">Abstract</x> Background: The existing shortage of animal models that properly mimic the progression of early-stage human lung cancer from a solitary confined tumor to an invasive metastatic disease hinders accurate characterization of key interactions between lung cancer cells and their stroma. We herein describe a novel orthotopic animal model that addresses these concerns and consequently serves as an attractive platform to study tumor–stromal cell interactions under conditions that reflect early-stage lung cancer. Methods: Unlike previous methodologies, we directly injected small numbers of human or murine lung cancer cells into murine's left lung and longitudinally monitored disease progression. Next, we used green fluorescent protein-tagged tumor cells and immuno-fluorescent staining to determine the tumor's microanatomic distribution and to look for tumor-infiltrating immune cells and stromal cells. Finally, we compared chemokine gene expression patterns in the tumor and lung microenvironment. Results: We successfully generated a solitary pulmonary nodule surrounded by normal lung parenchyma that grew locally and spread distally over time. Notably, we found that both fibroblasts and leukocytes are recruited to the tumor's margins and that distinct myeloid cell attracting and CCR2-binding chemokines are specifically induced in the tumor microenvironment. Conclusion: Our orthotopic lung cancer model closely mimics the pathologic sequence of events that characterizes early-stage human lung cancer propagation. It further introduces new means to monitor tumor–stromal cell interactions and offers unique opportunities to test therapeutic targets under conditions that reflect early-stage lung cancer. We argue that for such purposes our model is superior to lung cancer models that are based either on genetic induction of epithelial transformation or on ectopic transplantation of malignant cells.